106k views
2 votes
Solve: 2x+7/5 - x-3/10 = x+1/15
find the value of x and verify the result will RHS ​

Solve: 2x+7/5 - x-3/10 = x+1/15 find the value of x and verify the result will RHS-example-1
User XgMz
by
4.6k points

2 Answers

3 votes

Answer:

Explanation:

100+5

105

User Adam Skinner
by
4.4k points
5 votes

Explanation:

Given Question :-

Solve for x :-


(2x + 7)/(5) - (x - 3)/(10) = (x + 1)/(15)


\red{\large\underline{\sf{Solution-}}}

Given linear equation is


\rm :\longmapsto\: (2x + 7)/(5) - (x - 3)/(10) = (x + 1)/(15)


\rm :\longmapsto\: (2(2x + 7) - (x - 3))/(10) = (x + 1)/(15)


\rm :\longmapsto\: (4x + 14 - x + 3)/(10) = (x + 1)/(15)


\rm :\longmapsto\: ((4x - x) + (14 + 3))/(10) = (x + 1)/(15)


\rm :\longmapsto\: (3x + 17)/(10) = (x + 1)/(15)

On multiply by 5 on both sides,


\rm :\longmapsto\: (3x + 17)/(2) = (x + 1)/(3)

On cross multiplication, we get


\rm :\longmapsto\:3(3x + 17) = 2(x + 1)


\rm :\longmapsto\:9x +51 = 2x + 2


\rm :\longmapsto\:9x - 2x = 2 - 51


\rm :\longmapsto\:7x = - 49


\bf\implies \:x = - 7

VERIFICATION

Consider, LHS


\red{\rm :\longmapsto\: (2x + 7)/(5) - (x - 3)/(10)}

On substituting the value of x, we get


\red{\rm \:  =  \: (2( - 7) + 7)/(5) - ( - 7 - 3)/(10)}


\red{\rm \:  =  \: ( - 14 + 7)/(5) - ( - 10)/(10)}


\red{\rm \:  =  \: ( - 7)/(5) + 1}


\red{\rm \:  =  \: ( - 7 + 5)/(5)}


\red{\rm \:  =  \: ( - 2)/(5)}

Consider RHS


\green{\rm :\longmapsto\:(x + 1)/(15)}

On substituting the value of x, we get


\green{\rm \:  =  \: ( - 7 + 1)/(15)}


\green{\rm \:  =  \: ( - 6)/(15)}


\green{\rm \:  =  \: ( - 2)/(5)}


\rm \implies\:LHS=RHS

HENCE, VERIFIED

User Ambroz Bizjak
by
5.0k points